Education Management Implementation Course and Training Institutions in Improving Graduation Quality and Absorption in the World of Business and Industry (DUDI) - Slametno Slametno; Sofyan Sauri; Hendi Suhendraya Muchtar; Waska Warta (UIN Sunan Gunung Djati Bandung, 2019)
The implementation of education management for Course and Training Institutions in improving the quality of graduates and absorption in the Business and Industrial World (DUDI) is very much needed in order to sustain the existence of Course and Training Institutions due to the level of quality of graduates and absorption in the Business and Industrial World (DUDI) as indicators of prospective students. in choosing a Course and Training Institute (LKP).